The Effect of PhET-Assisted Problem Solving Method on Students' Critical Thinking skills - Ni Nyoman Sri Putu Verawati; Hikmawati Hikmawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to determine the effect of PhET-assisted problem solving methods on students' critical thinking skills. This research is a quasi-experimental research with pretest posttest control group design. Sampling was done by simple random sampling technique, namely class XI IPA-1 as the experimental class and XI IPA-2 as the control class. The research was conducted in one of the senior high schools in Central Lombok – West Nusa Tenggara. The data analysis technique used is t-test using SPSS. The result of hypothesis testing is that the t-test value is less than 0.05. These results indicate that Ho is rejected and Ha is accepted. Based on the results of research and data analysis, it can be concluded that the PhET-assisted problem solving learning method affects students' critical thinking skills.